Contact Allergy Cross-reactions and Thresholds: A Review. Issue 2 (2nd March 2022) - Scheman, Andrew; Ruggiero, Jenna L.; Kerchinsky, Lillian; Zippin, Jonathan H.; Zirwas, Matthew; Lugo-Somilinos, Aida; Hylwa, Sara
Abstract: Consideration of contact allergen concomitant reactivity, which encompasses cross-reactors, co-reactors, and pseudo cross-reactors, is an important aspect of patient care, yet information on how these terms are differentiated and used in clinical practice is lacking. In this review, we provide definitions of cross-reactors, coreactors, and pseudo cross-reactors and discuss the utility of the American Contact Dermatitis Society Contact Allergen Management Program database cross-reactor groupings. We also discuss limitations to the current categorization of cross-reactivity and recommend incorporating new terms, including "apparent cross-reactor" and "derivative cross-reactor, " when classifying cross-reactors.